REGULATION OF FIREARM OWNERSHIP FOR CIVILIANS IN INDONESIA BASED ON THE PRINCIPLE OF SELF-DEFENSE IN THE LEGAL PROTECTION SYSTEM (STUDY OF THE REPUBLIC OF INDONESIA LAW NUMBER 8 OF 1948 ON THE REGULATION OF THE INDONESIAN NATIONAL POLICE CHIEF NUMBER 82 OF 2004 - Asmariah Asmariah; Sukamto Kusnadi (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The need for legal protection for every human being is an undeniable matter. It is crucial to ensure that every citizen feels safe, and one of the efforts made by individuals to achieve this sense of security is by owning firearms. In the prevailing laws and regulations, civilians are allowed to possess firearms (firearms) as self-defense tools to protect themselves. In Indonesia, the law of self-defense is regulated in the Criminal Code (KUHP) Article 49. The following is an excerpt from Article 49 KUHP: